ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) TERHADAP KINERJA PERBANKAN (ROA) PADA PERUSAHAAN PERBANKAN PERIODE 2015-2016 - Sheilla Sheilla; Christiana Fara Dharmastuti (Prosiding Working Papers Series In Management, 2018)
The bank must have good health and improve its performance in order to gain the trust of the community. The rating of bank soundness is regulated by Bank Indonesia called RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). Therefore, this study aims to analyze bank soundness with RGEC method using NPL, GCG, OER, CAR, and bank book category as a moderating variable to banking performance (ROA). This research uses quantitative approach with multiple regression analysis method. The data used are secondary data from 66 banks operating in Indonesia during the period 2015-2016. Analysis of panel data using SPSS. The result is that all independent variables have no significant effect on ROA except OER variable and book category of bank does not moderate NPL, GCG and CAR relationship to ROA but moderate OER relationship to ROA.Keywords: Non Performing Loans, Good Corporate Governance, Operational Efficiency Ratio, Capital Adequacy Ratio, Return on Assets, RGEC, Bank soundness.